2014
DOI: 10.1371/journal.pone.0098734
|View full text |Cite|
|
Sign up to set email alerts
|

Tissue Engineering in Animal Models for Urinary Diversion: A Systematic Review

Abstract: Tissue engineering and regenerative medicine (TERM) approaches may provide alternatives for gastrointestinal tissue in urinary diversion. To continue to clinically translatable studies, TERM alternatives need to be evaluated in (large) controlled and standardized animal studies. Here, we investigated all evidence for the efficacy of tissue engineered constructs in animal models for urinary diversion. Studies investigating this subject were identified through a systematic search of three different databases (Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…In two systematic reviews we concluded that tissue engineering for urinary diversion or bladder augmentation should be performed in large animals, preferably in dogs or pigs (Sloff et al , ). In this study, a porcine model was chosen to compare the three different biomaterials in one animal, thereby eliminating inter‐animal variability.…”
Section: Discussionmentioning
confidence: 99%
“…In two systematic reviews we concluded that tissue engineering for urinary diversion or bladder augmentation should be performed in large animals, preferably in dogs or pigs (Sloff et al , ). In this study, a porcine model was chosen to compare the three different biomaterials in one animal, thereby eliminating inter‐animal variability.…”
Section: Discussionmentioning
confidence: 99%
“…At a time when transparency is becoming more and more important in preclinical studies and several authors attempt systematic reviews and meta-analyses using preclinical data [118,119], the role of precise and standardized reporting has to be heavily emphasized.…”
Section: Publication Guidementioning
confidence: 99%
“…In the paper by Sloff et al, all experiments describing the use of tissue engineering in urinary diversion construction conducted so far were evaluated [9]. They analyzed 8 works, of which 5 were related to urinary conduit and 3 to neo-bladder construction.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Urinary diversion can be divided into incontinent and continent (formed orthotopically or non-orthotopically). Incontinent ileocutaneostomy is most commonly used among surgeons and this type of urinary diversion has the greatest chances to be constructed using tissue engineering methods [9]. The use of an ileal segment, beside advantages such as maintaining ureter continuity together with urine outflow using autologous material with well developed blood supply, has number of disadvantages especially in the long-term follow-up [10,11,12].…”
Section: Introductionmentioning
confidence: 99%